Variation of hilbert coefficients - Ghezzi, Laura; Goto, Shiro; Hong, Jooyoun; Vasconcelos, Wolmer V (Proceedings of the American Mathematical Society, 2013)
For a Noetherian local ring (R, m), the first two Hilbert coefficients, e0 and e1, of the I-adic filtration of an m-primary ideal I are known to code for properties of R, of the blowup of Spec(R) along V (I), and even of their normalizations. We give estimations for these coefficients when I is enlarged (in the case of e1 in the same integral closure class) for general Noetherian local rings. © American Mathematical Society.
Keywords: dept.mat